Fiscal policy, conflict, and reconstruction in Burundi and Rwanda - Léonce Ndikumana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The ethnic conflicts in Burundi and Rwanda have severely weakened the economies and worsened the structural fiscal imbalances of these countries. Government revenue has declined due to the erosion of the tax base and tax administration capacity. At the same time, governments have shifted the allocation of resources from capital and social expenditures to military and security spending. This paper argues that there is a strong connection between a military-intensive fiscal policy stance and the lack of political legitimacy. A narrow-based regime tends to increase spending on security to increase its chances of survival. This strategy has dire social and economic consequences. In the long run, the economy may be caught in a “militarized poverty trap.” Fiscal stability is therefore contingent upon institutional reform aimed at establishing accountable and democratic governance.
Keywords: O23; O55; H56; 330; fiscal policy; conflict; sub-Saharan Africa; Finanzpolitik; Verteidigungshaushalt; Entwicklungshilfe; Schuldenerlass; Burundi; Ruanda